THE RELATION BETWEEN SELF-CONCEPT AND FOREIGN LANGUAGE ANXIETY - Isnaya Arina Hidayati (Jurnal Ilmiah Pesantren, 2017)
Foreign language anxiety is beliefs, feelings and complex behavior which related to language learning. Foreign language anxiety arising from internal factors, they are negative self-concept or perception of themselves. The aim of this research is to know the relation between self-concept with foreign language anxiety, to know the levels of self-concept and foreign language anxiety in college student of Boarding School K.H.Mas Mansyur-UMS. The types of this research is quantitative research, with the subject of research is college student of Boarding School K.H.Mas Mansyur-UMS totaling 65 students. The method of collecting data by using psychology scale; they are self-concept and foreign language anxiety scale with incidental sampling method. While the method of data analysis is by Product Moment analysis-Spearman. The result of this research proves that there is signifcant negative relation between self-concept with foreign language anxiety. The correlation coeffcient to (-0,343), it is mean the lower self-concept makes higher anxiety and vice versa. The variable of self-concept give an effective contribution of 11, 8% to the variable of foreign language anxiety. The categorization of foreign language anxiety is 77% and the categorization of self-concept is 88%. Then, the result proves that the levels of foreign language anxiety and self-concept of college student of Boarding School (Pesantren Mahasiswa) K.H.Mas Mansyur-UMS in average categorization